2021
DOI: 10.1111/acer.14704
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral economics of alcohol demand in Greek‐affiliated college students

Abstract: BackgroundCollege students affiliated with fraternity and sorority, or “Greek” life represent a known high‐risk group for alcohol consumption and related consequences, but little is known about demand for alcohol in this population. The current study examined behavioral economic demand for alcohol in a sample of Greek life‐affiliated undergraduate students using the alcohol purchase task (APT) and a novel variation of the APT that included a fixed‐price, nonalcoholic alternative (APT Choice).MethodsParticipant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, behavioral economic theory would suggest that tests of substitutability are a necessary step in identifying nondrug alternatives that would support sustained behavior change. While Ortelli and Martinetti (2021) provide preliminary evidence that this may not always be a necessary boundary condition for treatment, several caveats should be noted. Though prior research promoting substance-free alternative reinforcement has not formally assessed the economic substitutability of the alternatives, it is possible that the activities did function as substitutes, explaining positive treatment outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, behavioral economic theory would suggest that tests of substitutability are a necessary step in identifying nondrug alternatives that would support sustained behavior change. While Ortelli and Martinetti (2021) provide preliminary evidence that this may not always be a necessary boundary condition for treatment, several caveats should be noted. Though prior research promoting substance-free alternative reinforcement has not formally assessed the economic substitutability of the alternatives, it is possible that the activities did function as substitutes, explaining positive treatment outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…For all but three studies, the cross-commodity purchase tasks included only drugs as purchasable commodities. The exceptions were Murphy et al (2016; cigarettes and food items), Martinetti et al (2019; alcohol and nonalcoholic beverages), and Ortelli and Martinetti (2021; alcohol and nonalcoholic beverages). For most studies, at least one drug commodity of interest was nicotine ( n = 23) and/or tobacco ( n = 23), followed by cannabis ( n = 9), alcohol ( n = 9), and cocaine ( n = 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of a systematic review of these studies showed an array of orderly substitution or complementary relations between the alternative rewards (Weinsztok et al, 2022). A few studies have explored cross‐commodity relations between substances and nonsubstance alternatives (Martinetti et al, 2019; Murphy et al, 2016; Ortelli & Martinetti, 2021), with results generally demonstrating some element of substitutability. Similar findings have been reported in research on eating and access to alternative activities (Epstein et al, 2007).…”
Section: Human Laboratory Studies Of Temporal Discounting and Economi...mentioning
confidence: 99%